2020
DOI: 10.2174/1573401315666181128123332
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Fatty Acid Composition, Cholesterols, Triglyceride and Vitamin Contents of Some Selected Fishes from Assam, India

Abstract: Background: Fishes are good sources of the fatty acids such as ω-3 and ω-6 polyunsaturated fatty acids, and fat-soluble vitamins for human consumption which play vital roles for various biological processes in the body and help in the proper growth and prevention of diseases. Objective: The objective of the present study was to determine the fatty acid composition, cholesterols, triglyceride and vitamin contents of some selected fishes from Hel river, Assam, India. Methods: Fatty acid composition of fish s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Saturated, monounsaturated and polyunsaturated fatty acids were detected to be higher in C. gariepinus > Pseudotolithus typus > Pentanemus quinquairius > Tilapia zilli from Lagos lagoon [20]. Sarkar et al [23] reported that the most abundant fatty acids usually found in ten freshwater fishes of Hel river of Assam, India are myristic, palmitic, oleic, linoleic EPA and DHA acids. The major SFA (palmitic, Stearic and behenic acids), MUFA (oleic acid) and PUFA (linoleic acids) were reported four fishes of Hooghly estuary, West Bengal, India [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saturated, monounsaturated and polyunsaturated fatty acids were detected to be higher in C. gariepinus > Pseudotolithus typus > Pentanemus quinquairius > Tilapia zilli from Lagos lagoon [20]. Sarkar et al [23] reported that the most abundant fatty acids usually found in ten freshwater fishes of Hel river of Assam, India are myristic, palmitic, oleic, linoleic EPA and DHA acids. The major SFA (palmitic, Stearic and behenic acids), MUFA (oleic acid) and PUFA (linoleic acids) were reported four fishes of Hooghly estuary, West Bengal, India [24].…”
Section: Introductionmentioning
confidence: 99%
“…Ljubojevic et al [27] stated that "PUFAs in some fishes from Inland waters which varied from 17.07 to 28.15 %. Linoleic acid (omega -6) detected in nine fish species and was found to be the most abundant PUFAs and varied from 0.32 % in T. putitora to 27.21 % in N. Hexagonolepis" [23].…”
Section: Introductionmentioning
confidence: 99%